Spexin modulates the glucose homeostasis in streptozotocin (STZ)-induced diabetes in rat - ŞENER AKÇORA, DİLA (My University, 2023)
Background; Despite the various pharmacological agents and insulin treatment, still, there is lack of an effective and therapeutic treatment for diabetes. The present study investigated the possible therapeutic role of spexin (SPX) in glucose homeostasis both functionally and structurally in streptozotocin (STZ)-induced diabetic rats. Methods; Male Wistar albino rats(n=28) were randomly divided into the control(n=4), diabetes mellitus (DM+saline;1mL/kg, n=6), DM+S10(SPX;10 µg/kg/Ml, n=6), DM+S30(SPX; 30 µg/kg/mL, n=6) and DM+S100 (SPX; 100 µg/kg/mL, n=6). Diabetes was induced by administering a single dose of STZ (35mg/ kg, i.p. Blood and pancreatic tissue samples were taken for insulin level measurements by ELISA. Liver and muscle tissue samples were taken for glycogen measurement. Histopathological changes in liver, muscle and pancreas tissues were examined. Data were analyzed by ANOVA, and the Mann-Whitney-U test was used for multiple comparisons. Results; STZ-induced diabetes increased blood and urine glucose levels in the DM group as compared to the control group and significantly decreased with 10 mg/kg dose of SPX treatment. Glucose loss rate (K value) in insulin sensitivity measurements was lowered by STZ-induced diabetes (8.030) vs the control group (9.973) witha weak negative correlation (R=-0.1786). Glycogen content in liver and muscle tissues has declined, and SPX limited the decrease in hepatic glycogen levels in the DM+S10 group. SPX treatment reduced the degeneration levels and tissue damage in all tissues. Conclusions; Our findings indicated that SPX has a regulatory role in glucose homeostasis via insulin secretion, glycogen metabolism, and blood glucose regulation in a dose-dependent manner. Keywords: Spexin, diabetes, glucose, insulin, glycogen.

Amaç: Çeşitli farmakolojik ajanlar ve insülin tedavisine rağmen halen diyabetin etkili ve tedavi edici bir tedavisi bulunamamıştır. Bu çalışma, streptozotosin (STZ) ile indüklenen diyabetik sıçanlarda spexinin (SPX) glukoz homeostazisindeki olası terapötik rolünü hem fonksiyonel hem de yapısal olarak araştırdı. Gereç ve Yöntem: Erkek Wistar albino sıçanlar (n=28) rastgele olarak, kontrol (n=4), diyabet (DM+salin;1mL/ kg, n=6), DM+S10(SPX;10 µg/kg/Ml, n=6), DM+S30(SPX; 30 µg/kg/mL, n=6) ve DM+S100 (SPX; 100 µg/kg/ mL, n=6) gruplarına ayrıldı. Tek doz STZ (35mg/kg, i.p.) uygulanarak diyabet oluşturuldu. Kan ve pankreas dokusu örnekleri insülin düzeyinin ELISA ile ölçümü için alındı. Glikojen ölçümü için karaciğer ve kas dokusu örnekleri alındı. Karaciğer, kas ve pankreas dokularında histopatolojik değişiklikler incelendi. Veriler ANOVA ile analiz edilmiş ve çoklu karşılaştırmalarda Mann-Whitney-U testi kullanıldı. Bulgular: STZ ile indükelenen diyabet, DM+salin grubunda kontrol grubuyla karşılaştırıldığında kan ve idrar glukoz düzeyleri arttı ve 10 mg/kg SPX tedavisi ile anlamlı düzeyde azaldı. İnsülin duyarlılığı ölçümlerinde hesaplanan glikoz kaybolma oranı (K değeri), zayıf bir negatif korelasyonla (R=-0,1786) kontrol grubuna (9,973) kıyasla STZ kaynaklı diyabet (8,030) ile azaldı. Karaciğer ve kas dokularındaki glikojen içeriği azaldı ve SPX, DM+S10 grubunda hepatik glikojen seviyelerindeki düşüşü sınırladı. SPX tedavisi tüm dokulardaki dejenerasyon düzeylerini ve doku hasarını azalttı. Sonuç: Bulgularımız SPX’in insülin sekresyonu, glikojen metabolizması ve kan şekeri regülasyonu yoluyla glukoz homeostazisinde doza bağlı olarak düzenleyici bir role sahip olduğunu gösterdi.
Spexin, sıçanlarda streptozotosin (STZ) kaynaklı diyabette glukoz homeostazisini düzenler
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Spexin; diyabet; glukoz; insülin; glikojen